ANALISIS STRATEGI KAMPANYE KEMENANGAN PRABOWO GIBRAN PADA PEMILU 2024 DI KOTA TANGERANG SELATAN - Aryan Lesmana Putra; Endang Sulastri (Jurnal Riset Multidisiplin Edukasi, 2025)
The 2024 Indonesian Presidential Election marked one of the most dynamic moments in the nation’s democratic history, showcasing a transformation in political communication strategies and candidate personal branding. The Prabowo Subianto–Gibran Rakabuming Raka pair won the election in a single round with 58.6% of the national vote, including a significant 46.83% in South Tangerang City. This study aims to analyze the campaign strategy behind Prabowo–Gibran’s victory in South Tangerang, focusing on political communication approaches, social media utilization, and the creation of the “Prabowo Gemoy” image. The research applies a descriptive qualitative method, using in-depth interviews, documentation, and data triangulation from key informants, including local campaign teams, academics, voters, and the regional election commission (KPU). The findings reveal three major factors contributing to the victory: massive social media engagement to broaden political outreach, the “Gemoy” image that strengthened Prabowo’s humanistic and populist persona, and the effective mobilization of coalition party machinery at the regional level. These elements successfully connected with young voters and enhanced electability in urban areas. This study concludes that the integration of digital, narrative, and structural strategies represents an effective model for modern political campaigns in Indonesia’s local political context.